Evaluation of Physico-Chemical, Phytochemical, Minerals and Antimicrobial Properties from Selected Edible Fruits - Mukul Barwant; Nilesh Lavhate (International Journal of Research in Chemistry and Environment (IJRCE), 2019)
Fruit play a vital role in human nutrition, by supplying the necessary growth factors essential for maintaining normal health. In nature various types of plant and fruits are available these fruits are important for living things, the fruits containing organic and inorganic matter are present organic matter contains lipid, carbohydrates, vitamin C, protein, fats etc. The present investigation deals with evaluation of physic-chemical property, phytochemical analysis and antimicrobial activity. Analyses of fruit were carried out using Atomic Absorption Spectroscopy (AAS). The inorganic elements such as sodium, potassium, calcium, etc. these elements are major nutrients. Micronutrients such as magnesium, zinc, manganese, copper, iron etc. are essential nutrients for living organisms. The unripe species of all the fruits tend to have higher ascorbic acid content as shown in the results obtained, with sweet orange and lemon having almost twice the level of ascorbic acid than lime These elements are analyzed by various analytical techniques such as UV visible spectrophotometer, flame photometry and atomic absorptions spectrophotometry. Man has kept these commodities in his diet to provide variety, taste, interest, aesthetic appeal and to meet certain nutritional requirements world.